2015
DOI: 10.5527/wjn.v4.i1.127
|View full text |Cite
|
Sign up to set email alerts
|

Relationship ofMTHFRgene polymorphisms with renal and cardiac disease

Abstract: MTHFR gene polymorphisms could have a protective role on renal function as suggested by their lower frequency among our dialysis patients in end-stage renal failure; differently, the association with left ventricular hypertrophy and reduced left ventricular relaxation suggest some type of indirect, or concurrent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The DIVINe trial showed that treatment with FA (2.5 mg/day) and B vitamins (vitamin B 6 , 25 mg/day; cyanocobalamin, 1 mg/day) resulted in a greater decrease in GFR and an increase in vascular events in 238 patients with diabetic nephropathy [20]. A recent study on 630 Italian Caucasian population found a lower frequency of MTHFR 677C>T and A1298A>C polymorphisms among dialysis patients in end-stage kidney failure compared to subjects without or with slight-moderate renal impairment, suggesting a protective role of both polymorphisms on renal function [62]. …”
Section: Hhcy Fa and Renal Diseasementioning
confidence: 99%
“…The DIVINe trial showed that treatment with FA (2.5 mg/day) and B vitamins (vitamin B 6 , 25 mg/day; cyanocobalamin, 1 mg/day) resulted in a greater decrease in GFR and an increase in vascular events in 238 patients with diabetic nephropathy [20]. A recent study on 630 Italian Caucasian population found a lower frequency of MTHFR 677C>T and A1298A>C polymorphisms among dialysis patients in end-stage kidney failure compared to subjects without or with slight-moderate renal impairment, suggesting a protective role of both polymorphisms on renal function [62]. …”
Section: Hhcy Fa and Renal Diseasementioning
confidence: 99%
“…[8] Protective effects reported in cancer, renal failure or NAFLD, may suggest heterozygosis advantage. [9]In the local population, we observed a relatively high variant frequency in both patients and healthy controls, with no significantly increased MetS risk associated. [10] Hyperhomocysteinemia is often considered part of the MetS.…”
Section: Discussionmentioning
confidence: 83%
“…This study found that folic acid therapy significantly reduced stroke risk among participants with the CC or CT genotypes, but not among those with the TT genotype [34] and these results may extend to renal disease [35]. The association of MTHFR is complicated as SNPs, including rs13306561, rs1801133, and rs17367504, in the gene have been associated with increases in diastolic blood pressure, but these associations have not replicated across studies [36, 37].…”
Section: Genetic Polymorphism Dietary Choline and Metabolic Diseasementioning
confidence: 99%